2023
DOI: 10.1128/spectrum.02371-23
|View full text |Cite
|
Sign up to set email alerts
|

Heteroresistance to cefiderocol in carbapenem-resistant Acinetobacter baumannii in the CREDIBLE-CR study was not linked to clinical outcomes: a post hoc analysis

Christopher Longshaw,
Anne Santerre Henriksen,
Dana Dressel
et al.

Abstract: This study aimed to determine the proportion of heteroresistance in carbapenem-resistant Acinetobacter calcoaceticus-baumannii complex (CRAB) isolates in the cefiderocol arm of the randomized, Phase 3 CREDIBLE-CR study by population analysis profiling (PAP) and to determine whether there is any correlation between heteroresistance and clinical outcomes. PAP phenotypes [PAP-susceptible (PAP-S), PAP-heteroresistant (PAP-HR), or PAP-resistant (PAP-R)] were determined for baseline CRAB isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…In two correspondences, Choby et al, 2021 [ 9 , 10 ] suggested that these discrepancies might be due to cefiderocol-heteroresistant subpopulations not detected by standard AST. This hypothesis seems to be invalidated by the latest results from the CREDIBLE-CR study presented by Longshaw et al [ 11 ]. However, the apparently high rate of clinical or microbiological failure in some case series cannot be ignored, although other factors, such as clinical severity (septic shock) or strong immunosuppression, may influence these poor patient outcomes [ 6 , 12 ].…”
Section: Discussionmentioning
confidence: 98%
“…In two correspondences, Choby et al, 2021 [ 9 , 10 ] suggested that these discrepancies might be due to cefiderocol-heteroresistant subpopulations not detected by standard AST. This hypothesis seems to be invalidated by the latest results from the CREDIBLE-CR study presented by Longshaw et al [ 11 ]. However, the apparently high rate of clinical or microbiological failure in some case series cannot be ignored, although other factors, such as clinical severity (septic shock) or strong immunosuppression, may influence these poor patient outcomes [ 6 , 12 ].…”
Section: Discussionmentioning
confidence: 98%
“… 9–13 We found the prevalence of HR to be considerable among isolates with a susceptible MIC, with HR more likely among isolates with a higher baseline MIC. Although the impact on clinical outcomes remains unclear, 14–16 animal and some clinical studies have implicated HR in antibiotic failure. 8 Thus, ongoing surveillance for HR is warranted, as is continued investigation into its impact on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 8 There is conflicting evidence that HR can lead to antibiotic treatment failures, and most of these data come from studies of HR in Staphylococcus aureus 25–27 and Acinetobacter baumannii. 28–30 Furthermore, the lack of standardization of HR definitions and methods of detection, especially for Enterobacterales, has made understanding the relevance of HR in treatment failure problematic. 31 While there are limited data on the clinical implications of HR, animal studies have demonstrated failure of carbapenem therapy in HR Gram-negative bacilli infection models.…”
Section: Discussionmentioning
confidence: 99%